O processo de expansão e de interiorização do ensino superior no Instituto Federal da Paraíba : o caso do Campus Guarabira - Davi, Gutemberg de Lima (2024)
Given the historical situations of elitization of higher education and centralization of opportunities, located mainly in the country's large cities, it can be observed that there has been, in the last two decades, an inverse political-institutional movement that has given impetus to the possibility of access to higher education for social classes that have historically been excluded from academic life. After systematic provocations from sectors of society, between 2000 and 2015, the Federal government created some initiatives to democratize access, financing, expansion, permanence, inclusion and evaluation of higher education. This set of initiatives developed in parallel with the expansion and internalization of the Federal Institutes (IFs), an entity linked to the Ministry of Education (MEC) and the Secretariat of Professional and Technological Education (SETEC) that offers technical and higher education courses to Brazilian cities, especially those furthest from the capitals. In view of this scenario, this study presents an exploratory and descriptive research of a qualitative nature, with the general objective of analyzing the process of expansion and internalization of the Instituto Federal da Paraíba through the implementation of higher education courses at the Guarabira Campus. As specific objectives, the work intends to situate the historical-legal process of higher education in Brazil with emphasis on the Federal Institutes, as well as to reveal the development of the policy of expansion and internalization of higher education, describing the political, socioeconomic and institutional aspects in the process of installation of the Guarabira Campus of the Instituto Federal da Paraíba - IFPB, analyzing the possible relationships of its institutional actors and their relevant and determining factors for the implementation of the higher education courses offered at the unit. The study covered the period after the installation of the first higher education course at the Guarabira Campus in 2011, in phase III of the IFPB expansion, until the inauguration of the permanent headquarters in 2019. Based on the empirical field research, this work resulted in the development of a digital media product, in the form of an educational podcast, on the process of expansion and internalization of the IFPB Guarabira Campus, in addition to the analysis of institutional aspects aimed at assisting the IFPB management in improving the processes of implementing new decentralized units. Therefore, among the subjects interviewed in the research, the perception prevailed that there was no broad and in-depth discussion on the expansion of the IFPB and higher education, considering the political, socioeconomic, and academic aspects that influence the implementation of the Guarabira Campus. In view of the administrative experiences of the subjects researched, future institutional actions were suggested, such as more rigorous planning for the creation of new campuses, prioritizing consolidation rather than creating new units, reviewing and monitoring existing units in terms of academic efficiency and results, critically evaluating the policy of expansion and internalization of higher education, and ensuring broader participation of communities and local leaders in the process of discussing and introducing new units within the scope of the IFPB and in the offering of courses.